Meningkatkan Aktivitas Belajar PKn Siswa Kelas V.A SD Negeri 7 Cakranegara Tahun Pelajaran 2022/2023 - Yati, Mega Suci (TSAQOFAH, 2023)
The purposes of this study were to find out: 1) To find out that the SAVI learning approach can improve Civics learning activities in class V.A students at SD Negeri 7 Cakranegara in the 2022/2023 academic year; 2) To find out that the SAVI learning approach can improve Civics learning outcomes in class VA students at SD Negeri 7 Cakranegara for the 2022/2023 academic year. This research is a Classroom Action Research (CAR), using two cycles through the planning, action, observation, and reflection stages. As subjects in this study were students of class V.A for the 2022/2023 academic year with a total of 27 students, consisting of 16 male students and 11 female students. Based on the results of the classroom action research that has been carried out, the following conclusions can be drawn: The increase in student activity in Civics learning using the SAVI approach for class V.A students at SD Negeri 7 Cakranegara during cycle I to cycle II has increased. In the first cycle the score of students' improvement in learning was 66.67. In the implementation of cycle II, the score increased by 91.67, an increase of 25 points. The increase in teacher activity in implementing PPKn learning using the SAVI approach in class VA of SD Negeri 7 Cakranegara during the implementation of cycle I to cycle II continued to increase. In the first cycle, the teacher's ability to carry out learning was 73.68%. In cycle II the teacher's ability to carry out learning increased by 100%. In the implementation of cycle II the teacher's ability to carry out learning increased by 26.37 points. The increase in student learning outcomes obtained by the average Civics learning outcomes from the initial conditions to cycle II continued to increase. That the average student learning outcomes in the initial conditions is 62.96%. In cycle I, it increased by 18.52 points to 81.48%. Then in cycle II the average student learning outcomes increased by 18.52 points to 100%.